HUBUNGAN PENGETAHUAN IBU TENTANG MANFAAT PIJAT BAYI DENGAN TUMBUH KEMBANG ANAK 0-12 BULAN DI KLINIK ENO BABY SPA KECAMATAN BINJAI TAHUN 2023. - NINGSIH SAFARI, FIFI RIA; Bestari Sinaga, Eliza (Jurnal Kesehatan Ilmiah Aufa Royhan, 2024)
Infancy is the basis for a child's growth and development towards the next stage. This period is very dependent on parents and family in terms of providing basic needs for growth and development. Stimulation in infancy is very necessary to stimulate growth and development. Baby massage is an activity carried out by parents or baby caregivers as an act of stimulating the baby's growth and development. This study aims to determine the effectiveness of baby massage on the growth and development of 6 month old babies in the Bintaro sub-district, Jakarta. This research is a quantitative research with an experimental equation design with a non-randomized pre and post test approach with control group design. Respondents totaling 24 people were obtained using total sampling techniques. The instruments in this study used KPSP, meters and baby scales. Data analysis used univariate and bivariate (chi square test to get the odds ratio value and independent t-test to get the Eta Squared value). The research results showed that the value of the effectiveness of baby massage on development was calculated by looking at the odds ratio results. It was found that baby massage was 11 times greater for increasing the ability to lift the chest, 10 times greater for increasing the ability to lift the neck, the value of the effectiveness of baby massage for growth (weight and body length). ) calculated using the Eta Squared formula, the results were 0.28 for body weight and 0.43 for body length, which means that baby massage has great effectiveness in increasing children's growth and development in children 0-12 months